Housing and Young People Leaving Out-Of-Home State Care - Kunnen, Nola; Liddiard, Mark; Thoresen, Stian (University of New South Wales. City Futures Research Centre, 2010)
In Australia, there were over 34,000 young people in formal out of home state care such as foster care, group homes or state provided residential care in 2009. While many young people leave care before the age of 15, often to be reunited with their family, about 1,500 people “age out” of the care system between the ages of 15-17 every year. Australian and international research identifies young people with a care background as being at increased risk of social exclusion, including poor housing outcomes and homelessness. This paper presents data from an AHURI funded research project “Improving housing outcomes for young people leaving state out of home care”. Interviews were conducted between August 2008 and April 2009 in both Victoria and Western Australia. Qualitative and quantitative data was collected from young people aged 18 – 25 years who had experienced state care. The majority of participants interviewed were currently homeless or had experienced homelessness since leaving care. This paper presents a preliminary analysis of the quantitative data from this research reporting key findings including the incidence of exit planning for care leavers, together with homelessness and housing outcomes. The final report from this research will be completed in 2010.